LEXICO-SEMANTIC FEATURES OF PARALINGUISTIC UNITS IN ENGLISH - Bozorova O’g’iloy Qurbonali qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article addresses the issue of the lexico-semantic features of paralinguistic units in English spoken discourse and analyzes their contribution to changing lexical meaning. In recent years, linguistics pays increased attention to the multimodal aspect of spoken communication, recognizing that meaning is generated not only through verbal signs but also paralinguistic elements, such as intonation, stress, pitch, pauses, tempo, etc. The work relies upon the qualitative approach to description and interpretation. Examples of the paralinguistic interpretation of lexical units indicate that the same words might convey different ideas, depending on their prosodic performance (sincerity, sarcasm, sense of urgency, emotional involvement).